2009
DOI: 10.1002/bip.21262
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic basis for differential inhibition of the F1Fo‐ATPase by aurovertin

Abstract: The mitochondrial F 1 F o -ATPase performs the terminal step of oxidative phosphorylation. Small molecules that modulate this enzyme have been invaluable in helping decipher F 1 F o -ATPase structure, function, and mechanism. Aurovertin is an antibiotic that binds to the β subunits in the F 1 domain and inhibits F 1 F o -ATPase-catalyzed ATP synthesis in preference to ATP hydrolysis. Despite extensive study and the existence of crystallographic data, the molecular basis of the differential inhibition and kinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

6
3

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 54 publications
4
37
0
Order By: Relevance
“…A custom-made confocal microscope setup based on an Olympus IX 71 was used 40,41 for the triple-FRET measurements with single F O F 1 -ATP synthases. Three different lasers were applied: two fiber coupled picosecond pulsed lasers with arbitrary repetition rates up to 80 MHz at 488 nm (PicoTa 490, Picoquant) and 635 nm (LDH-P-635B, Picoquant) were used, and the third, continuous wave laser at 532 nm (compass 315, Coherent) was switched by a fast acusto optical modulator (AOM type 335-192, Crystal Technologies).…”
Section: Methodsmentioning
confidence: 99%
“…A custom-made confocal microscope setup based on an Olympus IX 71 was used 40,41 for the triple-FRET measurements with single F O F 1 -ATP synthases. Three different lasers were applied: two fiber coupled picosecond pulsed lasers with arbitrary repetition rates up to 80 MHz at 488 nm (PicoTa 490, Picoquant) and 635 nm (LDH-P-635B, Picoquant) were used, and the third, continuous wave laser at 532 nm (compass 315, Coherent) was switched by a fast acusto optical modulator (AOM type 335-192, Crystal Technologies).…”
Section: Methodsmentioning
confidence: 99%
“…Samples were then incubated for 5 min at 37°C with the conditions as follows: "apo," 5 mM The home-built microscope with expanded confocal detection volume of about 10 fl was described previously (31,32). Two lasers in duty cycle-optimized alternating fashion were used to excite the donor and acceptor (33).…”
mentioning
confidence: 99%
“…44 A previous study revealed that aurovertin inhibited ATPase considerably in the absence of F O and found that some protective action occurred in the presence of F O . 45 Furthermore, the gene encoding OSCP is involved in controlling respiration and regulates growth rate and body size, aging, and rates of behaviors such as pharyngeal pumping, defecation, and locomotion. Our results that the RNAi mutants in R53.4 or hpo-18 caused the nematodes to be more sensitive to aurovertin D were consistent with previous reports.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%